Effects of effort-reward imbalance, job satisfaction, and work engagement on self-rated health among healthcare workers - Jingjing Ge; Jing He; Yan Liu; Juying Zhang; Jingping Pan; Xueli Zhang; Danping Liu (BMC, 2021)
Abstract Background Healthcare workers, who protect and improve the health of individuals, are critical to the success of health systems and achieving national and global health goals. To respond effectively to the healthcare needs of populations, healthcare workers themselves must be in a good state of health. However, healthcare workers face various psychosocial pressures, including having to work night shifts, long working hours, demands of patient care, medical disputes, workplace violence, and emotional distress due to poor interactions with patients and colleagues, and poor promotion prospects. Constant exposure to these psychosocial hazards adversely impacts healthcare workers' health. Consequently, this study aimed to examine the influence of effort-reward imbalance, job satisfaction, and work engagement on self-rated health of healthcare workers. The results would be conducive to providing policy guidance to improve the health of healthcare workers. Methods We analysed the data of 1327 participants from The Chinese Sixth National Health and Services Survey in Sichuan Province that was conducted from August 2018 to October 2018. Structural equation modelling was used to test the hypothesized relationships among the variables. Results Only 40.1% of healthcare workers rated their health as 'relatively good' or 'good'. Effort-reward imbalance had a significant negative correlation with self-rated health (β = − 0.053, 95% CI [− 0.163, − 0.001]). The associations of effort-reward imbalance and work engagement with self-rated health were both mediated by job satisfaction (95% CI [− 0.150, − 0.050] and [0.011, 0.022]), and work engagement mediated the relationship between effort-reward imbalance and self-rated health (95% CI [− 0.064, − 0.008]). Conclusion In order to improve the health of healthcare workers, administrators should balance effort and reward and provide opportunities for career development and training. In addition, health managers should help healthcare workers realize the significance and value of their work and keep them actively devoted to their work through incentive mechanisms.